Patterns of open innovation within product development: a comparative study between Brazilian and Canadian aerospace industries. - Armellini, Fabiano (2013)
Open innovation is a new research line that emerges from a new industrial organization of research, development and innovation (R,D&I): after a period of vertical integration and accumulation, economy seems to walk towards a more plain level with lesser barriers to new entrants due to a new scenario of collaboration and knowledge dissemination. In this new mindset, firms can and should use external ideas as well as internal ideas, and internal and external paths to market, as firms look to advance in their technologies. The general goal of this research project is to analyze the depth and the impact of open innovation practices, as well as to identify patterns of their integration to the product development process (PDP) with focus on aerospace, a traditional high-tech segment within the metal-mechanic sector. For such, a reference model is elaborated and analyzed in two different contexts, in comparison study between Brazilian (emerging economy) and Canadian (developed economy) industries, more specifically the aerospace clusters in São Paulo and Quebec. The research comprises an aerospace market analysis, as well as the study of both countries national systems of innovation, supported by a survey that measures the intensity and importance of open innovation in Brazilian and Canadian aerospace companies plants. The survey is carried out by means of in-company questionnaire-based face interviews with R&D managers. The sample of analysis comprises a total of 53 aerospace plants, 22 of them in Brazil and 31 in Canada. Through a descriptive analysis of survey data, it is possible to identify similarities and differences in the patterns of open innovation in the two clusters. Among the similarities one highlights the focus on the product, the early involvement of customers in the PDP, the strategies adopted regarding intellectual property (IP) protection, the concentration of collaborative arrangements within the boundaries of the aerospace industry and the low intensity use of pecuniary tools, such as venture capital, spin-offs and/or acquisitions. Among the differences, Canada stands out with respect to its innovation public policies and assistance programs, which are found to be more effective in relation to Brazilian policies. Besides, Canadian plants seem to have a better innovative performance, at the cutting edge of aerospace technologies and higher international relevance. The survey also finds that the intensities of openness in Brazil and Canada are quite similar, although the patterns and motivations differ: Brazilian plants are more engaged in providing R&D services for products of third parties under direct contract (and not within collaborative arrangements) to local customers, while Canadian plants seem to be more engaged in a wider spam of collaborative fronts in a wider geographical range. Besides, Brazilian plants are much less intense in the adoption of formal IP protection methods in relation to Canadian ones, which hinders (but not prevents) the full adoption of open innovation in the Brazilian cluster. Based on the results, this text concludes with recommendations directed to the three vertices of the triple helix in both countries, namely: enterprises, science and technology institutes and the government.